VD_FINDINFO Jug / 2019 / 271 vom 15. April 2019 - VD Tribunal cantonal (2019)
DROIT D'ÊTRE ENTENDU, APPRÉCIATION DES PREUVES, ÉTAT DE NÉCESSITÉ, CIRCULATION ROUTIÈREDROIT DE LA CIRCULATION ROUTIÈRE | 17 CP, 18 CP, 29 al. 2 Cst., 31 LCR, 34 al. 3 LCR, 34 al. 4 LCR, 44 al. 1 LCR, 90 al. 1 LCR, 12 al. 1 OCR, 3 al. 1 OCR, 139 CPP (CH), 398 al. 4 CPP (CH)